EXPLORATION OF COSMIC SPIRITUAL EXPERIENCES AND ITS IMPLICATIONS FOR THE EVOLUTION OF TRANSPERSONAL CONSCIOUSNESS AMONG RELIGIOUS TOURISM VISITORS - Zulaikah, Enik; Khamami, Akhmad Rizqon Khamami Rizqon; Mahtukhin, Mahtukhin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to explore the cosmic spiritual experiences experienced by religious tourism visitors and their implications for the evolution of transpersonal consciousness. Cosmic spiritual experiences are phenomena characterized by feelings of deep connection with transcendent reality, awareness beyond ego identity, and individual psychological and existential transformation. This study uses the method Systematic Literature Review (SLR) to analyze various previous studies that discuss the phenomenon of spiritual experiences, transpersonal awareness, and their impacts in the context of religious tourism. The research results show that cosmic spiritual experiences in religious tourism can occur through various factors, such as a supportive spiritual environment, religious rituals, and individual psychological readiness. This experience contributes to increased transpersonal awareness, which is characterized by a sense of universal connectedness, increased empathy, and a change in life orientation towards deeper meaning. In addition, this research found that integrating spiritual experiences in daily life is a challenge for individuals. In conclusion, cosmic spiritual experiences have great potential in developing transpersonal consciousness, but require social support and spiritual guidance. Therefore, it is recommended that religious tourism provide reflective and educational programs to assist individuals in understanding and internalizing their spiritual experiences.